What Drives Corporate Governance Reform? Firm-Level Evidence from Eastern Europe - Klapper, Leora F.; Laeven, Luc; Love, Inessa (World Bank, Washington, DC, 2012)
The authors study differences in the use of two corporate governance provisions - cumulative voting and proxy by mail voting - in a sample of 224 firms located in four Eastern European countries. The report finds a significant relationship between ownership structure, and the use of corporate governance provisions. Firms with a controlling owner (owning more than 50 percent of shares) are less likely to adopt either of the two provisions. However, firms that have large, minority shareholders are more likely to adopt these provisions. The authors do not find any significant relationship between the use of these provisions, and foreign ownership. The results suggest that the decision to adopt these corporate governance provisions is influenced by large, minority shareholders in their battle for representation in the board, and in managerial decisions.